FILM DOKUMENTER WISATA RELIGI BASAPA DI ULAKAN, KABUPATEN PADANG PARIAMAN - YOSI HANDAYANI, Ir. Drs. Heldi, M.Si, Ishakawi, S.Pd., M.Ds (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Basapa is a year tradition in visiting a sacred place likely Syekh Burhanuddin in Ulakan, Padang Pariaman which is celebrated on Syafar 10th. Syekh Burhanuddin was known as disseminator of Tarekat Syattariah and Islam in Minangkabau. Syekh Burhanuddin passed away on Syafar 10th, 1111 H/1691 M. Demise of late Syekh Burhanuddin was on Syafar, so the ritual is known as basapa.The lack of inhabitants knowledge and promotion media about basapa is the main factor of the writer for creating the documentary film in order to promote pilgrimage tourism basapa. The pilgrimage tourism basapa which is promoted in documentary film is for making easy to the people to know more about basapa tradition and conversing the value. Besides documentary film, this promotion is also supported the others media, such as clothes, calendar, banner, stickers, clocks, pins, key rings, CD covers, CD labels, and mugs.The methodology is 5W+1H analysis, what, who, when, where, why, and how. By applying this theory, all of aspects have been covered about basapa and created in documentary film, so that it can be a medium that has effective and communicative factual information.Key words: documentary film, pilgrimage tourism, basapa.